Occupational Health and Its Influence on Job (Dis)Satisfaction - Almeida, Fernando (2019)
Occupational health provides/promotes the highest level of physical, mental, and social well-being of the working class in all occupations; protects workers at their place of work, against any risk factor that is detrimental to their health; safeguards all kinds of damage to workers’ health caused by working conditions and adapts the type of work to the physical and psychological fit ness of each individual. This study discusses the concepts of job satisfaction and absenteeism, setting as goal the assessment of his importance in the workplace (occupational health). This study was conducted with 149 profes sionals from Portugal, encompassing several professional categories. The re sults show significant differences in the levels of job satisfaction, according variables such as professional category, working hours, motivation, and satis faction. The results suggest the need for programs that promote wages per ceived as fair and adequate benefit policies, in order to achieve improvements at both organizational and individual levels.